Electroacupuncture enhances extragonadal aromatization in ovariectomized rats - Chen Boying; Cheng Lina; Tian Zhanzhuang; Zhao Hong (BMC, 2004)
Abstract Background Repeated electroacupuncture (EA) stimulation is known to stimulate the activity of the hypothalamus-pituitary-adrenal axis, and to enhance the circulation level of estrogen in the ovariectomized rats. To explore the source of the increased circulation estrogen, the extragonadal aromatization was detected. Methods Female rats were divided into five groups: 1) intact (INT), 2) intact with EA in specific points (INT+EA), 3) ovariectomized (OVX), 4) ovariectomized with EA in specific points (OVX+EA) and 5) ovariectomized with EA in non-specific points (OVX+C). Radiometric assay, Western blot and RT-PCR were adopted to determine the extragonadal aromatization in subcutaneous abdominal (SA) adipose and liver tissues of rats. The blood concentrations of estrogen, testosterone and corticosterone were measured by radioimmunoassay. Results The aromatase activities of the SA adipose and liver tissues in the OVX+EA rats increased significantly (p < 0.01) compared with those in the INT, INT+EA and OVX rats. The 58-kDa aromatase protein and aromatase mRNA expressions normalized to β-actin in the OVX+EA rats' SA adipose tissues showed higher levels than those from corresponding tissues in the INT and INT+EA rats (p < 0.05). And the ratios of aromatase mRNA and protein to β-actin in the OVX+EA rats' liver tissues increased significantly compared with those in the OVX rats (p < 0.05). Furthermore, blood estrogen and corticosterone concentrations showed significant increase in the OVX+EA rats compared with the concentrations in the OVX and OVX+C rats (p < 0.05), but no statistical disparity occurred on the blood testosterone concentrations between the OVX+EA rats and the OVX ones. Conclusion Both the subcutaneous abdominal adipose and the liver tissues contributed to the effects of electroacupuncture on the extragonadal aromatization to promote the blood concentrations of estrogen in the ovariectomized rats.